(-)-Syringaresinol-4-O-β-D-glucopyranoside from Cortex Albizziae inhibits corticosterone-induced PC12 cell apoptosis and relieves the associated dysfunction. (July 2020) - Yang, Desen; Wu, Wanqin; Gan, Guoping; Wang, Dingkun; Gong, Jing; Fang, Ke; Lu, Fuer
Abstract: The neuroprotective effects and potential mechanisms of (-)-Syringaresinol-4-O-β-D-glucopyranoside (SRG), a natural lignan glycoside extracted from Cortex Albizziae, were investigated using corticosterone (CORT)-induced PC12 cells as an in vitro anxiety model. PC12 cells were treated with 100 μM CORT and 5, 10, or 20 μM SRG for 48 h. Cell viability and lactate dehydrogenase (LDH) leakage were measured. Apoptosis were detected using FITC-coupled Annexin V (AV) and propidium iodide (PI) staining flow cytometric analyses and TUNEL assays. Rhodamine 123 and Fluo-3-AM staining flow cytometric analyses were used to detect mitochondrial membrane potential (ΔΨm) and intracellular calcium concentration ([Ca 2+ ]i ), respectively. Western blot was used to detect brain-derived neurotrophic factor (BDNF), Bax, Bcl-2, cAMP-response element binding protein (CREB), cytosolic cytochrome c (Cyt c ), caspase-3, and cleaved caspase-3. Experimental data showed that SRG promoted cell proliferation, reduced LDH release, inhibited apoptosis, improved ΔΨm values, decreased [Ca 2+ ]i, up-regulated CREB, BDNF, and Bcl-2, down-regulated Bax and Cyt c protein expression levels, and reduced caspase-3 activity. This suggests that SRG has neuroprotective and antiapoptotic effects in the pathogenesis of anxiety disorders, and its mechanisms are partly connecte to inhibition of the mitochondrial apoptotic pathway and activation of pathways involving CREB and BDNF. Highlights: (-)-Syringaresinol-4-O-β-D-glucopyranoside (SRG) from Cortex Albizziae is an anti-anxiety active ingredient. The neuroprotective and antiapoptotic effects of SRG on an in vitro anxiety models showed its potential as anxiolytic. The roles of SRG in the anti-anxiety mechanism were partly related to CREB-BDNF and mitochondrial apoptosis pathway.